ANALISIS PENGARUH AGRESIVITAS PAJAK TERHADAP CASH HOLDING DAN NILAI PERUSAHAAN - Anisa, Nurul; Muid, Dul (Diponegoro Journal of Accounting, 2017)
This study was aimed to examine the effect of corporate tax aggressiveness on the amount of firm cash holding and the value of the company. Book-Tax Difference is used as a measure of corporate tax aggressiveness. The cash flow sensitivity of cash is used to measure the amount of cash holding and Tobin’s Q is used to measure the value of the company.The population in this study is all manufacturing companies listed in Indonesia Stock Exchange in 2015. Sampling method in this research is purposive sampling. The final total amount of samples in this study were 109 companies.After going trough the stages of data processing and analysis techniques used are multiple regression analysis. The analysis showed that independent variable of taxaggressiveness does not affect the amount of cash holding. But the results of the further analysis indicatethat tax aggressiveness affect the value of the company.